Genetic Evidence for Distinct Functions of Peptidoglycan Endopeptidases in Escherichia coli - Park, Si Hyoung; Kim, Yung Jae; Lee, Han Byeol; Seok, Yeong-Jae; Lee, Chang-Ro (Frontiers in Microbiology, 2020)
Peptidoglycan (PG) is an essential component of the bacterial exoskeleton that plays a pivotal role in the maintenance of cell shape and resistance to cell lysis under high turgor pressures. The synthesis and degradation of PG must be tightly regulated during bacterial cell elongation and division. Unlike enzymes involved in PG synthesis, PG hydrolases show high redundancy in many bacteria including Escherichia coli. In this study, we showed that PG endopeptidases have distinct roles in cell growth and division. Phenotypic analysis of mutants lacking one of seven PG endopeptidases identified a MepM-specific phenotype, salt sensitivity, and a MepS-specific phenotype, EDTA sensitivity. Complementation test in each phenotype showed that the phenotype of the mepM mutant was restored only by MepM, whereas the phenotype of the mepS mutant was restored by MepS or by overexpression of MepH, PbpG, or MepM. These distinct phenotypes depend on both the specific localizations and specific domains of MepM and MepS. Finally, using the identified phenotypes, we revealed that MepM and MepH affected both penicillin-binding protein 1a (PBP1a) and PBP1b, whereas MepS and PbpG affected only PBP1b. Notably, a defect in PBP1a or PBP1b phenocopied the mepM mutant, suggesting the importance of MepM on PG synthesis. Therefore, our results indicate that each PG endopeptidase plays a distinct role in cell growth and division, depending on its distinct domains and cellular localizations.